Case Report: The Alzheimer’s paradox: a clinically stable amnestic syndrome with full biomarker positivity and minimal imaging evidence - Balageas, Anna-Chloé; Vercouillie, Johnny; Arlicot, Nicolas; Dupont, Anne-Claire; Santiago Ribeiro, Maria-Joao (Frontiers in Medicine, 2025)
We report the case of a 75-year-old patient with a clinically isolated and stable amnestic syndrome over fifteen years, despite a cerebrospinal fluid (CSF) profile strongly consistent with Alzheimer’s disease (AD). Serial PET imaging over two years showed only limited amyloid accumulation, no significant tau deposition, no hypometabolism, and no neuroinflammation. This case illustrates a striking dissociation between biomarker positivity and clinical progression, raising important questions about individual resilience and the prognostic value of AD biomarkers in isolation.